2019
DOI: 10.1097/ta.0000000000002560
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions after nonoperative trauma: Increased mortality and costs with delayed intervention

Abstract: Background:We sought to examine patterns of readmission after non-operative trauma, including rates of delayed operative intervention and mortality. Methods:The Nationwide Readmissions Database (2013Database ( -2014 was queried for all adult trauma admissions and 30-day readmissions. Index admissions were classified as operative (OI) or nonoperative (NOI), and readmissions examined for major operative intervention (MOR). Multivariable regression modeling was used to evaluate risk for readmission requiring MOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The current body of literature evaluating readmissions among trauma patients has focused on association with particular injury patterns, 26 patient characteristics, 3 discharge destination, 23 time to intervention, 27 and inpatient laboratory markers. 28 However, the current study suggests that the readmissions that are most likely to be prevented may not be associated or may even be inversely associated with the severity of the patient's injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The current body of literature evaluating readmissions among trauma patients has focused on association with particular injury patterns, 26 patient characteristics, 3 discharge destination, 23 time to intervention, 27 and inpatient laboratory markers. 28 However, the current study suggests that the readmissions that are most likely to be prevented may not be associated or may even be inversely associated with the severity of the patient's injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite similar social determinants being present, the findings of cost analysis will likely be unique in different hospital systems depending on the availability of individual community resources. 7,9,10,[22][23][24][25] While some papers have standardized costs to "Medicare" costs, our patient population was generally too young to apply this method. Additionally, hospital cost does not provide information regarding reimbursement.…”
Section: Limitations and Next Stepsmentioning
confidence: 99%
“…6 Analysis of acute care costs has been successful in identifying differences within the general trauma population. 5,7 Julliard 8 et al used hospital costs to compare the utility of hospital-based interventions, making it an attractive baseline for a needs assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found that 4%–14% of adult trauma patients returned to the hospital within 30 days of discharge, with the most common reasons being inadequate pain control, wound complications, uncontrolled comorbid health conditions, or psychosocial factors (Killien et al., 2021; Petrey et al., 2015; Shellito et al., 2020). Posthospitalization complications and readmission are costly and associated with increased patient mortality (Flood et al., 2013; McCrum et al., 2020; Neiman et al., 2021).…”
mentioning
confidence: 99%